Comprehensive degaussing treatment method for 304 austenitic stainless steel

Through the integrated demagnetization treatment method of multi-technology collaboration, the problems of low demagnetization efficiency and unstable effect of 304 austenitic stainless steel in the prior art are solved, and an efficient, uniform and stable demagnetization effect is achieved, which meets the strict requirements of high-end equipment for magnetism, and maintains the comprehensive performance of the material.

CN119776633APending Publication Date: 2025-04-08YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411975040.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing 304 austenitic stainless steel demagnetization technology has the problems of large energy consumption, long processing time and unstable effects. Especially in areas with strict magnetic requirements, it is difficult to meet the needs of efficient, uniform and stable demagnetization.

Method used

A comprehensive demagnetization treatment method with multiple technologies is adopted, including pretreatment, high-temperature solid solution optimization treatment, cold deformation treatment, pulse magnetic field reverse demagnetization strengthening treatment and laser demagnetization treatment. Through precise parameter control and close coordination of each step, an efficient, uniform and stable demagnetization effect is achieved.

Benefits of technology

It realizes efficient demagnetization of 304 austenitic stainless steel, with stable magnetic strength below 0.1Gs, avoiding magnetic interference, improving the stability and reliability of the equipment, and maintaining the comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776633A_ABST
    Figure CN119776633A_ABST
Patent Text Reader

Abstract

The invention provides a comprehensive degaussing treatment method for 304 austenitic stainless steel, which adopts a multi-technology collaborative degaussing treatment method and comprises high-temperature solid solution optimization treatment, cold deformation treatment, pulsed magnetic field reverse degaussing strengthening treatment and laser degaussing treatment. The degaussing effect is more efficient, uniform, stable and reliable, and meanwhile the comprehensive performance of the material is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of austenitic stainless steel manufacturing, and in particular relates to a comprehensive demagnetization treatment method for 304 austenitic stainless steel. Background Art

[0002] 304 austenitic stainless steel is widely used in industrial production and high-end equipment manufacturing. However, in some fields with strict requirements on magnetism, such as electronic precision instruments, high-precision medical devices, and peripheral components of magnetic resonance imaging equipment, even trace amounts of residual magnetism can affect equipment operation and detection accuracy.

[0003] Existing 304 austenitic stainless steel demagnetization technologies, such as thermal demagnetization, require the material to be heated to a high temperature and kept warm for a long time before slowly cooling. This method consumes a lot of energy, takes a long time to process, and is prone to large differences in demagnetization effects due to uneven heating and cooling. Although the AC demagnetization method disorderes the magnetic domains through an alternating magnetic field, it requires multiple adjustments to the magnetic field parameters and extended processing time, resulting in low efficiency and unstable results. Summary of the invention

[0004] In view of this, the present invention aims to propose a comprehensive demagnetization treatment method for 304 austenitic stainless steel, which adopts a multi-technology collaborative demagnetization treatment method, and achieves a more efficient, uniform, stable and reliable demagnetization effect through close coordination of each step and precise parameter control, while maintaining the comprehensive performance of the material.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A comprehensive demagnetization treatment method for 304 austenitic stainless steel, the method comprising the following steps:

[0007] S1. Preprocessing

[0008] First, the oil stains on the surface of 304 austenitic stainless steel are removed by combining organic solvent wiping and ultrasonic cleaning, and then the surface oxide layer of the material is treated by combining chemical pickling and mechanical grinding;

[0009] S2. High temperature solution optimization treatment

[0010] The pretreated material is placed in a heat treatment furnace with high-precision temperature control and uniform heating functions to heat up, and after reaching the set temperature, it is kept warm so that the structure is evenly transformed into austenite; after the insulation is completed, the material is immediately water quenched;

[0011] S3. Cold deformation treatment

[0012] The material after high temperature solid solution optimization treatment is subjected to cold rolling, cold drawing or cold forging to cause plastic deformation of the material, and the deformation is controlled within 10%-30%;

[0013] Cold deformation treatment can introduce a large number of crystal defects such as dislocations, which will affect the magnetic domain structure and facilitate further adjustment of the magnetic domains during subsequent pulse magnetic field reverse demagnetization strengthening treatment and laser demagnetization treatment, thereby improving the demagnetization effect; at the same time, by reasonably controlling the amount of cold deformation, excessive deformation can be avoided to cause material hardening and performance deterioration, ensuring that the material can still maintain good comprehensive performance after demagnetization;

[0014] S4, pulse magnetic field reverse demagnetization strengthening treatment

[0015] After the cold deformation treatment, a professional pulse magnetic field generator is used to apply a pulse magnetic field to the material. The device is equipped with a high-precision magnetic field strength adjustment system and a frequency control module, which can accurately output the required magnetic field strength and frequency. The direction of the pulse magnetic field is opposite to the direction of the residual magnetic field of the material. The direction of the residual magnetic field can be pre-determined with the help of an advanced magnetic field detection sensor, and then the pulse magnetic field generator automatically adjusts the output magnetic field direction, and the material must be located at the center of the magnetic field.

[0016] S5. Laser degaussing

[0017] The scanning path is designed according to the shape, size and demagnetization requirements of the components. The components are fixed on a high-precision processing platform with a six-axis linkage function, and the position and posture of the components are precisely adjusted to ensure accurate laser scanning. The laser parameters are adjusted, and then the laser is used to scan the material surface to quickly raise the temperature to above the austenite transformation temperature (850-950℃) and maintain the temperature for less than 1 millisecond.

[0018] Further, the temperature in S2 is raised to 1050-1200°C at a heating rate of 2-6°C / min. This heating rate can prevent the material from generating excessive thermal stress due to too fast heating, while ensuring that the internal structure is evenly heated and fully austenitized; the temperature is kept for 60-240min to allow the alloy elements in the material to fully diffuse, the structure to evenly transform into austenite, and the structure to optimize, laying the foundation for subsequent magnetic reduction;

[0019] The magnetic field strength of the pulsed magnetic field in S4 is in the range of 650-700 Gs, the frequency is 15-16 Hz, and the pulsed magnetic field is applied continuously for 45-50 minutes; Step S4 preliminarily reduces the magnetic properties of the material. This parameter range has been verified by a large number of experiments to effectively promote the rearrangement of the magnetic domains inside the material without destroying the microstructure of the material;

[0020] In S5, 1064nm or 532nm high-power pulsed laser is selected. These two wavelengths of laser are easily absorbed by 304 austenitic stainless steel to produce thermal effects; the pulse energy is set at 0.5-2J, the pulse width is controlled at 10-50 nanoseconds, and the repetition frequency is set at 1-10kHz.

[0021] Further, the specific steps of S1 are:

[0022] S11. Soak the material in an organic solvent and gently rub the surface with a soft brush to remove tightly attached oil impurities; then put it in an ultrasonic cleaning machine with an ultrasonic frequency of 30-50kHz for 10-15 minutes to further remove fine oil particles and ensure that the surface of the material is clean;

[0023] S12. Soak the material treated in S11 in mixed acid, then gently polish it along the material texture with sandpaper manually or with a mechanical polishing device to remove the loose oxide layer and surface scratches remaining after the acid treatment, to ensure that the material surface is flat and smooth, creating conditions for subsequent processing.

[0024] Pretreatment can improve the efficiency and effect of subsequent demagnetization treatment and reduce the adverse effects of surface impurities on magnetic field and material organization transformation.

[0025] Furthermore, the organic solvent used in S11 is environmentally friendly ethanol or acetone.

[0026] Furthermore, the mixed acid solution used in S12 includes 10%-15% by mass of nitric acid, 5%-8% by mass of hydrofluoric acid and the balance of water, the soaking time is 5-10 minutes, and the particle size of the sandpaper is 200-400 meshes.

[0027] Furthermore, the cooling water temperature is 20-30°C and the water flow rate is 5-10m / s, which can not only ensure rapid cooling of the material and inhibit the formation of magnetic phases such as ferrite and martensite, but also avoid defects such as cracks caused by too rapid cooling, further reduce the magnetism of the material, and ensure good mechanical properties.

[0028] Furthermore, the positioning error of the material in the magnetic field is controlled within ±1mm, which is achieved through a combination of laser positioning, mechanical micro-adjustment and other technologies.

[0029] Further, the scanning path in S5 includes the following methods:

[0030] For parts with regular shapes, a uniform scanning method is used to perform laser scanning along a regular path with equal spacing and angles to ensure that the surface of the material is evenly heated;

[0031] For special-shaped parts with complex surfaces, internal holes or thin-walled structures, a combination of partition scanning and overlapping scanning is adopted.

[0032] Furthermore, the specific scanning method for special-shaped parts is: first divide them into several relatively regular areas according to their structural characteristics, plan the scanning path in each area, and set 2-5mm overlapping scanning areas in adjacent areas to ensure that the demagnetization effect of the entire component is uniform.

[0033] During the laser scanning process, a high-precision infrared thermometer (temperature measurement accuracy ±1°C) is used to monitor the surface temperature in real time, and the data is fed back to the laser control system to dynamically adjust parameters such as laser power and scanning speed to ensure a stable and efficient demagnetization process.

[0034] Compared with the prior art, the comprehensive demagnetization treatment method for 304 austenitic stainless steel of the present invention has the following advantages:

[0035] 1. Efficient demagnetization

[0036] By optimizing the processing sequence and precise parameter control, the present invention can reduce the magnetism of 304 austenitic stainless steel to an extremely low level, with the magnetic strength stably below 0.1Gs. In actual application tests, the treated components were used in electronic precision instruments and equipment without magnetic interference, effectively avoiding the interference of magnetism on the operation of the equipment, improving the stability and reliability of the system, and meeting the strict requirements of high-end equipment for magnetism.

[0037] 2. Maintain the comprehensive performance of materials

[0038] The present invention first cleans the stainless steel material through pretreatment, which can improve the efficiency and effect of subsequent demagnetization treatment and reduce the adverse effects of surface impurities on the magnetic field and material organization transformation. Reasonable temperature control operation in high-temperature solid solution optimization treatment enables the organization to be uniformly transformed into austenite, optimizes the organizational structure, improves the material processing performance, makes the internal organization more uniform and fine, and provides good mechanical properties for subsequent mechanical processing, which is the basis for subsequent demagnetization operations. Defects such as dislocations introduced by cold deformation treatment are helpful for magnetic domain adjustment in the subsequent demagnetization process, and reasonable control of deformation can avoid performance deterioration. Pulse magnetic field reverse demagnetization strengthening treatment achieves demagnetization by applying a reverse magnetic field to offset the magnetic field of the material itself. Laser demagnetization further eliminates the residual magnetic field from a microscopic perspective by sending a laser to the material. When the laser is irradiated to the magnetic material, the electron spin angular momentum of the material will be rapidly transferred to the atoms of the lattice, causing the magnetism of the material to disappear rapidly. Pulse magnetic field reverse demagnetization combined with laser demagnetization can achieve full demagnetization of both under relatively mild conditions, reducing the internal damage to the material caused by the accumulation of thermal effects. At the same time, pulse demagnetization first makes up for the insufficient elimination efficiency of more staggered magnetic domains when directly using laser demagnetization to demagnetize materials after cold deformation. Laser demagnetization can supplement the problem of insufficient precise demagnetization of pulse demagnetization under milder conditions, while reducing the internal stress accumulation caused by pulse demagnetization. Pulse magnetic field reverse demagnetization strengthening treatment and laser demagnetization treatment have little effect on the mechanical properties (tensile strength, yield strength, elongation, etc.) and corrosion resistance of materials due to precise parameter selection. The mechanical performance index of the demagnetized material is within ±5% compared with the un-demagnetized material of the same specification. The corrosion resistance is tested according to the standard salt spray test, and the corrosion rate does not change by more than 10%, ensuring that the demagnetized material still has good comprehensive performance and meets the strict requirements of high-end equipment for material performance.

[0039] 3. Wide applicability

[0040] The demagnetization treatment method of the present invention is applicable to parts of various shapes, and can achieve efficient and uniform demagnetization effect by reasonably designing treatment parameters, such as laser scanning path, magnetic field parameters, etc. It has been tested and applied in high-end manufacturing fields such as electronics, medical treatment, aerospace, etc., providing technical support for the large-scale application of 304 austenitic stainless steel in magnetic sensitive fields and promoting the development of related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0042] Figure 1 This is the morphology of the complex-shaped component after demagnetization treatment in Example 1;

[0043] Figure 2 This is the appearance of the large flat plate-shaped component after demagnetization treatment in Example 2;

[0044] Figure 3 This is the morphology after comparative example 1 was treated only with the traditional thermal demagnetization method;

[0045] Figure 4 This is the morphology after comparative example 2 was treated only with the conventional AC demagnetization method;

[0046] Figure 5 This is the morphology of Example 4 after the lack of laser demagnetization treatment. DETAILED DESCRIPTION

[0047] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0048] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0049] Example 1 Demagnetization of complex-shaped parts

[0050] Material selection: 304 austenitic stainless steel parts with complex internal cavities and curved surfaces used in high-end medical equipment have extremely high requirements for magnetic properties, surface properties and overall reliability.

[0051] The degaussing process is as follows:

[0052] S1. Preprocessing:

[0053] S11. Surface cleaning: Soak the parts in environmentally friendly ethanol, wipe the surface with a soft brush to remove tightly attached oil and impurities, and then put them into an ultrasonic cleaning machine with an ultrasonic frequency of 40kHz for 12 minutes to further remove fine oil particles and ensure the cleanliness of the material surface.

[0054] S12, oxide layer removal: prepare a mixed acid solution containing 12% (mass fraction) nitric acid, 6% (mass fraction) hydrofluoric acid and the remainder of water, and use the mixed acid solution to soak the material treated by S11 for 8 minutes, so that the oxide layer and the acid solution can fully react and dissolve, and then use 300-mesh sandpaper to manually polish along the material texture direction to remove the loose oxide layer and surface scratches remaining after the acid treatment, to ensure that the material surface is flat and smooth, and to create conditions for subsequent treatment. Pretreatment can improve the efficiency and effect of subsequent demagnetization treatment, and reduce the adverse effects of surface impurities on the magnetic field and material organization transformation.

[0055] S2. High temperature solution optimization treatment:

[0056] The pretreated material was placed in a heat treatment furnace with high-precision temperature control and uniform heating functions, heated to 1100°C at 3°C / min, kept warm for 180 minutes, and then water quenched at 22°C and a water flow rate of 7m / s.

[0057] S3. Cold deformation treatment:

[0058] The cooled parts are cold deformed by cold rolling, and the deformation is controlled at 15%.

[0059] S4, pulse magnetic field reverse demagnetization strengthening treatment:

[0060] The processed parts are precisely placed in the center of the pulsed magnetic field through a combination of laser positioning, mechanical micro-adjustment and other technologies, with an error of ±0.5mm. The direction of the pulsed magnetic field is exactly opposite to the direction of the residual magnetic field of the material. The direction of the residual magnetic field is pre-determined with the help of advanced magnetic field detection sensors, and then the pulsed magnetic field generating device automatically adjusts the output magnetic field direction, adjusting the magnetic field strength to 660Gs, the frequency to 15Hz, lasting for 46min and monitoring the magnetic changes.

[0061] S5. Laser degaussing treatment:

[0062] For parts with complex shapes, a combination of partition scanning and overlapping scanning is used. First, the parts are divided into several relatively regular areas according to their structural characteristics, and scanning paths are planned in each area. Adjacent areas are set with 2-5mm overlapping scanning areas to ensure uniform demagnetization effect of the entire part.

[0063] Fix the component on a high-precision processing platform, select a 532nm laser, set the pulse energy to 1.5J, the pulse width to 20 nanoseconds, the repetition frequency to 8kHz, and scan along the path. During the laser scanning process, use a high-precision infrared thermometer (temperature measurement accuracy ±1°C) to monitor the surface temperature in real time, and feed the data back to the laser control system to dynamically adjust parameters such as laser power and scanning speed to ensure a stable and efficient demagnetization process.

[0064] Effect: After treatment, the magnetic strength of the parts is less than 0.05Gs, and there is no obvious damage on the surface, such as Figure 1 The surface hardness varies within the range of ±8HV, the roughness varies within the range of ±0.3μm, and the mechanical properties and corrosion resistance remain good, meeting the high-precision operation requirements of high-end medical equipment.

[0065] Example 2 Demagnetization of large flat plate-shaped components

[0066] Material selection: Large flat-plate 304 austenitic stainless steel components used in electronic semiconductor manufacturing are selected, which have strict requirements on magnetic uniformity and low magnetism.

[0067] The degaussing process is as follows:

[0068] S1. Preprocessing:

[0069] S11. Surface cleaning: Soak the parts in acetone as an organic solvent, wipe with a soft brush, and then perform ultrasonic cleaning for 13 minutes at a frequency of 45kHz.

[0070] S12, oxide layer removal: prepare a mixed acid solution containing 13% nitric acid, 7% hydrofluoric acid and the remainder water, soak the material treated by S11 in the mixed acid solution for 8 minutes, and then mechanically polish it along the grain direction of the material with 250-grit sandpaper.

[0071] S2. High temperature solution optimization treatment:

[0072] The pretreated material was placed in a heat treatment furnace with high-precision temperature control and uniform heating functions, heated to 1180°C at 5°C / min, kept at that temperature for 100 minutes, and then water quenched and cooled. The water temperature was 28°C and the water flow rate was 9m / s.

[0073] S3. Cold deformation treatment:

[0074] The cooled parts are cold deformed by cold drawing, and the deformation is controlled within 20%.

[0075] S4, pulse magnetic field reverse demagnetization strengthening treatment:

[0076] The processed parts are precisely placed in the center of the pulsed magnetic field through a combination of laser positioning, mechanical micro-adjustment and other technologies, with an error of ±0.8mm. The direction of the pulsed magnetic field is exactly opposite to the direction of the residual magnetic field of the material. The direction of the residual magnetic field is pre-determined with the help of advanced magnetic field detection sensors, and then the pulsed magnetic field generating device automatically adjusts the output magnetic field direction, adjusting the magnetic field strength to 690Gs and the frequency to 15.5Hz for 47min while monitoring the magnetic changes.

[0077] S5. Laser degaussing treatment:

[0078] For parts with regular shapes, a uniform scanning method is used. After fixing the parts, a 1064nm laser is selected with a pulse energy of 1.8J, a pulse width of 35 nanoseconds, and a repetition frequency of 6kHz. The temperature is controlled during scanning and monitored with an infrared thermometer.

[0079] Effect: The magnetic strength of the treated parts is uniform and less than 0.08Gs. The morphology after demagnetization is as follows: Figure 2 The entire flat surface has good magnetic consistency and excellent processing performance, and can effectively avoid magnetic interference when used in electronic semiconductor equipment.

[0080] Example 3 Demagnetization of small precision parts

[0081] Material selection: Select small 304 austenitic stainless steel precision parts in precision electronic equipment, which have strict requirements on surface accuracy and low magnetism.

[0082] The degaussing process is as follows:

[0083] S1. Preprocessing:

[0084] S11. Surface cleaning: Soak and wipe with ethanol, then ultrasonically clean for 14 minutes at an ultrasonic frequency of 48 kHz.

[0085] S12. Removal of oxide layer: prepare a mixed acid solution containing 14% nitric acid, 7.5% hydrofluoric acid and the remainder water, soak for 6 minutes, and then manually polish along the material texture direction with 350-grit sandpaper.

[0086] S2. High temperature solution optimization treatment:

[0087] The precision parts were placed in a heat treatment furnace, heated to 1120°C at 4°C / min, kept at that temperature for 150 minutes, and then quenched in water at a water temperature of 25°C and a water flow rate of 8m / s.

[0088] S3. Cold deformation treatment:

[0089] The cold forging process is used to produce 12% cold deformation on precision parts.

[0090] S4, pulse magnetic field reverse demagnetization strengthening treatment:

[0091] The precision components are accurately placed in the center of the pulsed magnetic field with an error of ±0.3mm. The direction of the pulsed magnetic field is exactly opposite to the direction of the residual magnetic field of the material. The direction of the residual magnetic field is pre-determined with the help of advanced magnetic field detection sensors, and then the pulsed magnetic field generating device automatically adjusts the output magnetic field direction, adjusts the magnetic field strength to 670Gs, the frequency to 16Hz, lasts for 45min, and monitors the magnetic changes.

[0092] S5. Laser degaussing treatment:

[0093] Design a scanning path suitable for small components, fix it on a high-precision processing platform, use a 1064nm laser, pulse energy 1.0J, pulse width 15 nanoseconds, repetition frequency 10kHz, strictly control laser parameters and temperature, and monitor with an infrared thermometer.

[0094] Effect: After treatment, the magnetic strength of precision components is less than 0.06Gs, the surface accuracy is maintained well, and the surface hardness and roughness change very little, meeting the performance requirements of precision electronic equipment for components.

[0095] Comparative Example 1: Only using traditional thermal demagnetization method

[0096] Processing process: The 304 austenitic stainless steel parts same as those in Example 1 were heated to 1050°C and then naturally air-cooled.

[0097] Effect: After demagnetization, the appearance is as follows Figure 3 As shown, the magnetic strength fluctuates between 3-7Gs, the grain growth is uneven, residual stress is generated, the tensile strength is reduced by about 10%, the yield strength is reduced by about 12%, the hardness is uneven, the tool wear is aggravated, and the surface roughness is increased, which cannot meet the needs of high-precision applications.

[0098] Comparative Example 2: Only using the traditional AC demagnetization method

[0099] Treatment process: The 304 austenitic stainless steel parts same as those in Example 1 were placed in an alternating magnetic field and demagnetized to zero at 10 Gs / min.

[0100] Effect: For parts with complex shapes, the difference in magnetic strength in different parts can reach more than 6Gs. After treatment, the lowest magnetic strength can only reach about 1.8Gs, which will cause magnetic interference problems in high-precision applications.

[0101] Comparative Example 3: Combination of high temperature solid solution optimization treatment and AC demagnetization method (lack of pulse magnetic field reverse demagnetization strengthening treatment)

[0102] Treatment process: firstly, the same component as that in Example 1 is subjected to high temperature solid solution optimization treatment (with the same parameter range as that in Example 1), and then the component is placed in an alternating magnetic field and demagnetized to zero at 10 Gs / min.

[0103] Effect: After treatment, the magnetic strength can be reduced to a certain extent, but there are still some areas with high magnetic strength, about 0.5-1.2Gs, and the demagnetization uniformity of complex-shaped parts is poor, which cannot meet the requirements of high-end medical equipment and ultra-high precision electronic equipment. The material performance retention effect is not as good as the combined treatment method of the present invention.

[0104] Comparative Example 4: Combination of high temperature solid solution optimization treatment and pulse magnetic field reverse demagnetization strengthening treatment (lacking laser demagnetization treatment)

[0105] Processing process: First, the same components as in Example 1 are subjected to high-temperature solid solution optimization treatment (with the same parameter range as in Example 1), and then pulse magnetic field reverse demagnetization strengthening treatment (with the same parameter range as in Example 1) is performed.

[0106] Effect: The magnetic strength can be reduced to a lower level, but there is still weak magnetism in some local areas of the material surface. The uniformity of surface performance is not as good as that of complete combination treatment. It may not meet the requirements in the application of precision electronic equipment shells with extremely high surface performance requirements. For example, the surface hardness range can reach ±15HV, and the roughness range can reach ±0.8μm.

[0107] Comparative Example 5 High temperature solution optimization treatment conditions are different

[0108] A-High rate: The difference from Example 1 is that the temperature in S2 is raised to 1100°C at 8°C / min, and the other steps are the same as Example 1.

[0109] Effect: After treatment, the magnetic strength of the parts is between 2-4Gs, and there is still weak magnetism in some local areas on the surface of the material. This is because the heating rate is too fast and the austenitization inside the organization is uneven, resulting in uneven demagnetization.

[0110] B- low rate: the difference from Example 1 is that the temperature in S2 is raised to 1100°C at 1°C / min, and the other steps are the same as Example 1.

[0111] Effect: After treatment, the magnetic strength of the parts is between 1-5Gs, and there is still weak magnetism in some local areas on the surface of the material. This is because the heating rate is too slow and the austenitization inside the organization is uneven, resulting in uneven demagnetization.

[0112] Comparative Example 6: Different cold deformation amounts

[0113] A-large deformation: The difference from Example 1 is that the deformation amount in S3 is 50%, and the other steps are the same as Example 1.

[0114] Effect: The magnetic strength of the treated parts is between 7-10Gs, and due to the excessive deformation, the material hardens and the mechanical properties deteriorate, which cannot meet the requirements of high-end medical equipment and ultra-high precision electronic equipment.

[0115] B-small deformation: The difference from Example 1 is that the deformation amount in S3 is 5%, and the other steps are the same as Example 1.

[0116] Effect: After treatment, the magnetic strength of the parts is between 1-3Gs, and some areas still have higher magnetic strength, about 4-6Gs. Although the deformation is too small and will not affect the mechanical properties, the demagnetization is uneven and cannot meet the requirements of high-end medical equipment and ultra-high precision electronic equipment.

[0117] Comparative Example 7 Pulse magnetic field reverse demagnetization strengthening treatment conditions are different

[0118] A-Low magnetic field strength and low frequency: The difference from Example 1 is that the magnetic field strength in S4 is 600 Gs, the frequency is 12 Hz, and the duration is 46 min. The other steps are the same as Example 1.

[0119] Effect: After treatment, the magnetic strength of the parts is between 1-1.5Gs. Low magnetic field strength and low frequency cannot effectively eliminate the residual magnetic field.

[0120] B-High magnetic field strength and high frequency: The difference from Example 1 is that the magnetic field strength in S4 is 750 Gs, the frequency is 20 Hz, and the duration is 46 min. The other steps are the same as Example 1.

[0121] Effect: After treatment, the magnetic intensity can be reduced to a certain extent, about 0.2Gs, but there are still some areas with high magnetic intensity, about 1Gs or more. Although increasing the magnetic field strength and frequency can indeed improve the effectiveness of demagnetization, it is worth noting that if the intensity of the reverse magnetic field is set too high, it may cause the material to be given a reverse magnetic field during the demagnetization process, thereby causing the material to regain its magnetism. This phenomenon will not only interfere with the subsequent laser demagnetization steps, but may also have an adverse effect on the final demagnetization effect. Therefore, in actual operation, it is necessary to fine-tune the magnetic field parameters to avoid such situations.

[0122] Comparative Example 8 Laser Degaussing Treatment Conditions Different

[0123] High pulse energy and high frequency: The difference from Example 1 is that the pulse energy in S5 is 3J, the frequency is 15kHz, the pulse width is 15 nanoseconds, and the other steps are the same as Example 1.

[0124] Effect: The magnetic intensity can be reduced to a lower level, but there is still weak magnetism in some local areas on the surface of the material. The pulse energy and frequency may be high, which will affect the electron spin angular momentum of the material and is not conducive to the demagnetization of the material.

[0125] Comparative Example 9: Different demagnetization order

[0126] The difference from Example 1 is that laser demagnetization treatment is performed first, and then pulse magnetic field reverse demagnetization and strengthening treatment is performed. The other steps are the same as Example 1.

[0127] Effect: Although the magnetic intensity can also be reduced to a lower level, it is still higher than that in Example 1, about 0.3-0.5Gs. The pulse magnetic field reverse demagnetization first performs overall demagnetization, and the laser demagnetization further demagnetizes from a microscopic perspective. If the order of the two is swapped, the demagnetization effect will be affected.

[0128] Through the comprehensive analysis of the above embodiments and comparative examples, it can be clearly seen that the demagnetization treatment method proposed by the present invention shows wide applicability to components of various shapes. The method combines multiple demagnetization technologies to implement comprehensive demagnetization treatment on the components. By carefully designing and optimizing the processing parameters, including but not limited to the scanning path of the laser and various parameters of the magnetic field, we have successfully achieved an efficient and uniform demagnetization effect, ensuring that the magnetic strength of the treated components is stably maintained at a low level below 0.1Gs.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A comprehensive demagnetization treatment method for 304 austenitic stainless steel, characterized by: The method comprises the following steps: S1. Preprocessing First, the oil stains on the surface of 304 austenitic stainless steel are removed by combining organic solvent wiping and ultrasonic cleaning, and then the surface oxide layer of the material is treated by combining chemical pickling and mechanical grinding; S2. High temperature solution optimization treatment The pretreated material is placed in a heat treatment furnace for heating, and after reaching the set temperature, it is kept warm so that the structure is evenly transformed into austenite; after the insulation is completed, the material is immediately water quenched; S3. Cold deformation treatment The material after high temperature solid solution optimization treatment is subjected to cold rolling, cold drawing or cold forging to cause plastic deformation of the material, and the deformation is controlled within 10%-30%; S4, pulse magnetic field reverse demagnetization strengthening treatment After cold deformation, a pulsed magnetic field is applied to the material. The direction of the pulsed magnetic field is opposite to the direction of the residual magnetic field of the material, and the material must be located at the center of the magnetic field. S5. Laser degaussing Design the scanning path according to the shape, size and demagnetization requirements of the component, fix the component on the processing platform, adjust the laser parameters, and then use the laser to scan the material surface so that the temperature quickly rises to above the austenite transformation temperature and the holding time is less than 1 millisecond.

2. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 1, characterized in that: In S2, the temperature is raised to 1050-1200°C at a rate of 2-6°C / min and kept at this temperature for 60-240min; The magnetic field strength of the pulsed magnetic field in S4 is in the range of 650-700Gs, the frequency is 15-16Hz, and the pulsed magnetic field is applied continuously for 45-50min; In S5, a 1064nm or 532nm high-power pulsed laser is selected, the pulse energy is set at 0.5-2J, the pulse width is controlled at 10-50 nanoseconds, and the repetition frequency is set at 1-10kHz.

3. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 1, characterized in that: The specific steps of S1 are: S11. Soak the material in an organic solvent, and gently rub the surface with a soft brush to remove tightly attached oil impurities; then put it in an ultrasonic cleaning machine with an ultrasonic frequency of 30-50kHz for cleaning for 10-15 minutes; S12. Soak the material treated in S11 in mixed acid, then gently polish it along the material texture with sandpaper manually or with a mechanical polishing device to remove the loose oxide layer and surface scratches remaining after the acid treatment, and ensure that the surface of the material is flat and smooth.

4. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 3, characterized in that: The organic solvent used in S11 is environmentally friendly ethanol or acetone.

5. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 3, characterized in that: The mixed acid solution used in S12 includes 10%-15% nitric acid, 5%-8% hydrofluoric acid and the balance water in mass percentage. The soaking time is 5-10 minutes, so that the oxide layer reacts and dissolves with the acid solution fully. The particle size of the sandpaper is 200-400 mesh.

6. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 1, characterized in that: The cooling water temperature in S2 is 20-30°C, and the water flow rate is 5-10m / s.

7. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 1, characterized in that: In S4, the positioning error of the material in the magnetic field is controlled within ±1mm.

8. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 1, characterized in that: The scanning path in S5 includes the following methods: For parts with regular shapes, a uniform scanning method is used to perform laser scanning along a regular path with equal spacing and angles to ensure that the surface of the material is evenly heated; For special-shaped parts with complex surfaces, internal holes or thin-walled structures, a combination of partition scanning and overlapping scanning is adopted.

9. The comprehensive demagnetization treatment method for 304 austenitic stainless steel according to claim 8, characterized in that: The specific scanning method for special-shaped parts is: first divide them into several relatively regular areas according to their structural characteristics, plan the scanning path in each area, and set 2-5mm overlapping scanning areas in adjacent areas to ensure uniform demagnetization effect of the entire component.